93.1k views
4 votes
If f(x)=-3x-5 and g(x)=4x-2,find (f-g)(x)

User Beseder
by
5.2k points

2 Answers

2 votes

f(x) = -3x - 5, g(x) = 4x - 2

(f - g)(x) = f(x) - g(x) = (-3x - 5) - (4x - 2) = -3x - 5 - 4x + 2 = (-3x - 4x) + (-5 + 2)

(f - g)(x) = -7x - 3

User Pedro Manfredi
by
5.2k points
5 votes

Answer: The required value is


(f-g)(x)=-7x-3.

Step-by-step explanation: The given functions are:


f(x)=-3x-5\\\\g(x)=4x-2.

We are to find the value of
(f-g)(x).

We know that, for any functions s(x) and t(x), we have


(s-t)(x)=s(x)-f(x).

Therefore, we get


(f-g)(x)\\\\=f(x)-g(x)\\\\=(-3x-5)-(4x-2)\\\\=-3x-5-4x+2\\\\=-7x-3.

Thus, the required value is


(f-g)(x)=-7x-3.

User Oskar Krawczyk
by
5.6k points